An Ionospheric Climate Index Based on GNSS - Cheng Wang; Yuting Li; Jicang Wu; Lei Fan; Zhipeng Wang; Chen Zhou; Chuang Shi (Space Weather)
Abstract The ionospheric total electron content (TEC) is a significant parameter for scientific studies of the ionosphere and space weather. Ground‐based Global Navigation Satellite System (GNSS) station network provides an opportunity for modeling the ionospheric TEC with high accuracy. Based on global ionospheric TEC maps, by using data from the International GNSS Service (IGS) stations for 21 years (from 1998 to 2018), we establish an ionospheric climate index (ICI) for representing the general state of the ionosphere. In addition, we build a multiple linear regression model for fitting ICI using the SSN, F10.7, Ap, and Dst indices and upper atmospheric wind field. We quantitatively analyze the contribution of these factors to ICI time series. ICI during the past six solar cycles, namely, from 1958 to 2018, are presented, which are assigned as the adjectives (cold, cool, mild, warm, hot, and sizzling) for ionospheric climatology studies. This new index is a very promising representative of day‐to‐day variations of middle‐ and low‐latitude ionosphere.